(untitled) (Indian Journal of Nematology, 2024)
Columbia lance nematode (Hoplolaimus columbus Sher, 1963) was identified among the samples collected from the rhizosphere of three host plants viz., Jackfruit (Artocarpus heterophyllus), Mango (Mangifera indica) and Tea (Camellia sinensis), and three geographical locations viz., Lakhimpur, Nagaon and Karbi Anglong districts of Assam from the banana rhizosphere. Morphology and morphometric variations were recorded among the populations. The species was identified as H. columbus based on the number of lip annuli (3-4) in the lip region and longitudinal lines (10-15) in the basal annulus, SE pore posterior to the nerve ring and hemizonid 2-5 annuli behind the secretary-excretory pore, six gland nuclei in oesophageal glands, phasmids on either side of the vulva, number of tail annuli (13-22), and morphometric values. Morphometric observations in females of H. columbus showed that body length, length of the oesophagus, stylet length, anal body width, the distance of the secretary-excretory pore, nerve ring, median bulb, and oesophageal gland overlapping from the anterior end, a, b, V%, median bulb, and Pp (per cent of the distance of posterior phasmid from anterior end to body length) were least variable characters (CV < 10). The characters such as tail length, number of tail annuli, body width, bʹ, c, cʹ, and Pa (anterior phasmid) were variable (CV > 10) to both hosts and geographical locations. Thus, this study confirms that H. columbus being a parthenogenetic species, shows the least morphometric plasticity and is not much induced by the hosts and geographic locations. Further, low intraspecific variations indicate no cryptic speciation in H. columbus.